ANALISIS KRITIS TERHADAP IMPLEMENTASI PERLINDUNGAN LAHAN PERTANIAN PANGAN BERKELANJUTAN - Dahiri Dahiri (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2021)
The conversion of agricultural paddy fields to non-paddy fields is estimated at100,000 hectares per year. If the conversion of productive land functions is notresolved, it is estimated that in the next 40-50 years, the rice field area will be usedup as non-agricultural areas. The purpose of this study is to analyze the factorsthat can affect sustainable food agriculture land and the efforts that need to bemade by the government to protect sustainable food agricultural land. Theresearch method used to descriptive statistics and normative juridical approach.The results show that there is no incentive for local governments to include PLP2Bin their RTRW, incentives for farmers who are committed to PLP2B, and financingin extensification development activities not based on the IKK. Therefore, thegovernment's efforts to protect sustainable food agricultural land are providingincentives for local governments to determine the area of sustainable foodagriculture in the RTRW with incentives in the form of DAK in agriculture, providingincentives for farmers who participate in PLP2B by providing pre-harvest and postharvestagricultural machine tools, and calculation of extensification costs usingthe IKK.